The Effect of the Simplified Contribution Pension Plan on the Probability of Voluntary Contributions to the Pension System in Brazil - Foguel, Miguel N.; Moreira, Ajax; Santos, Daniel (Estudos Econômicos (São Paulo), 2012)
In April 2007 aiming at increasing participation of self-employed workers in the public pension system the Brazilian government launched the Plano Simplificado de Previdência Social (PSPS) – Simplified Pension Plan. The plan allows a reduction of the contributory percentage from 20% to 11% for any self-employed worker who decided to contribute exactly on the value of the minimum wage. Those who opt for the plan can only retire through the age criterion. The main goal of this paper was to verify whether the PSPS had an impact on the probability of voluntary contribution to the social security system of non-formal workers. To reach that goal, we use a random sample extracted from the Cadastro Nacional de Informações Sociais (CNIS) - Social Information National Register , an administrative database that contains information on the history of social security contributions of all workers. The method employed to estimate the impact was the well-known difference-in-differences approach. The results show that the PSPS seems to have increased the probability of voluntary contribution of workers whose base of contribution is the minimum wage.